2014
DOI: 10.1186/1752-1947-8-276
|View full text |Cite
|
Sign up to set email alerts
|

Identification of a novel COL2A1 mutation (c.1744G>A) in a Japanese family: a case report

Abstract: IntroductionMutations in the gene encoding the type II collagen gene (COL2A1) have been found to affect the entire skeletal system. Recently, inheritable skeletal dysplasia caused by novel COL2A1 mutations has been linked to an inherited disease of the hip joint that neither involves the entire skeletal system nor is characterized by the presence of concomitant disorders, such as spinal or ocular abnormalities.Case presentationA 27-year-old Japanese woman previously diagnosed with avasucular necrosis (AVN) of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 6 publications
0
11
0
Order By: Relevance
“…P.Gly1170Ser was subsequently found in two Chinese families in 2014 and 2018 . Moreover, p.Gly582Ser was identified in patients with ANFH …”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“…P.Gly1170Ser was subsequently found in two Chinese families in 2014 and 2018 . Moreover, p.Gly582Ser was identified in patients with ANFH …”
Section: Resultsmentioning
confidence: 97%
“…47,95 Moreover, p.Gly582Ser was identified in patients with ANFH. 96 Legg-Calve-Perthes disease (LCPD; MIM #150600) is a form of ANFH in children; its peak incidence occurs between the ages of 4 and 8 years. The average age of five cases of LCPD was 6.15 years old.…”
Section: Types Mainly Involved In Long Bone and Joint Disordersmentioning
confidence: 99%
“…There is an interesting report on one family with hip disorders. 18 In this family, multiple family members including the proband had initially been diagnosed as idiopathic ONFH. However, careful observations for imaging findings led correct diagnosis of the proband as not idiopathic ONFH but epiphyseal dysplasia, and COL2A1 mutation was identified eventually.…”
Section: Discussionmentioning
confidence: 97%
“…Thus, if we encounter the family in which multiple members are affected by hip disorders, we should suspect the possibility of skeletal dysplasia first. There is an interesting report on one family with hip disorders . In this family, multiple family members including the proband had initially been diagnosed as idiopathic ONFH.…”
Section: Discussionmentioning
confidence: 99%
“…However, in the present study, no similar mutations were detected in one of the family members (subject II-1), which strongly indicates that acquired factors may have an irreversible role in the pathogenesis of ANFH. Additionally, it was reported that a c.4148G>A ( 18 ) or c.1774G>A mutations ( 19 ) in the COL2A1 gene may also lead to familial ANFH. Notably, evidence from clinical studies has demonstrated that a single base substitution in the COL2A1 gene is also implicated in the development of LCPD ( 8 , 14 , 25 ) and premature hip OA, which are two other types of type II collagenopathies ( 16 , 27 ).…”
Section: Discussionmentioning
confidence: 99%